2019
DOI: 10.3390/atmos10030137
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Air Quality during a Festival Season in Kannur, India

Abstract: This study looked at the variation in air quality during the periods of fireworks as assessed from the change in ambient concentrations of air pollutants like particulate matter (PM10), O3, and NO2 for pre-, post-, and Vishu days for four consecutive years in 2015, 2016, 2017, and 2018 in Kannur, India. Enhanced levels of O3, NO2, NO, and PM10 were observed during the intense usage of fireworks. The concentration of metals in PM10 increased and the percent increase was found to be different for metal traces. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In addition, the NO 2 level increased, unlike in the present study, and this change may be related to the NO 2 photolysis rates shown in the modeling. [23] In recent years, the chemical components released into the atmosphere from various sources caused air pollution of PM indifferent sizes as one of the problems of utmost importance in terms of public health that needs to be solved. [24] The United Nations International Children's Emergency Fund published a report indicating that 600.0000 children die each year in developing countries due to insufficient air quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NO 2 level increased, unlike in the present study, and this change may be related to the NO 2 photolysis rates shown in the modeling. [23] In recent years, the chemical components released into the atmosphere from various sources caused air pollution of PM indifferent sizes as one of the problems of utmost importance in terms of public health that needs to be solved. [24] The United Nations International Children's Emergency Fund published a report indicating that 600.0000 children die each year in developing countries due to insufficient air quality.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different types of pollutants involved in the overall atmospheric aerosol contamination, short-lasting but active point sources of pollution should also be considered [12,13], which include fireworks shows [14]. This is one of the most unusual sources of air pollution, which has been investigated quite frequently and on a large scale in the literature [15][16][17] which allows the identification of specific pollutants related only to the burning of fireworks [18,19]. Although the show associated with the New Year celebrations only takes place once a year, it has a very significant impact on the air quality.…”
Section: Introductionmentioning
confidence: 99%